Murder, the media, and the politics of public feelings: remembering Matthew Shepard and James Byrd Jr - Petersen, Jennifer (Indiana Univ. Press, 2011)
Introduction: media, emotion, and the public sphere -- Mourning Matthew Shepard: grief, shame, and the public sphere -- "Hate is not a Laramie value": translating feelings into law -- The murder of James Byrd Jr.: the political pedagogy of melodrama -- The visibility of suffering, injustice, and the law -- Conclusion: feeling in the public sphere